Solace of the road - Dowd, Siobhan (Oxford : David Fickling Books, 2010)
While running away from a London foster home just before her fifteenth birthday, Holly has ample time to consider her years of residential care and her early life with her Irish mother, whom she is now trying to reach.
Young Adult.
Young Adult
Keywords: Foster home care -- Juvenile fiction; Hitchhiking -- Juvenile fiction; Missing persons -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Foster home care -- Fiction; Hitchhiking -- Fiction; Runaways -- Fiction; Self-actualization (Psychology) -- Fiction; Voyages and travels -- Fiction; Foster home care -- Fiction; Hitchhiking -- Fiction; Missing persons -- Fiction; Self-realization -- Fiction; Voyages and travels -- Fiction; Great Britain -- Juvenile fiction; Great Britain -- Fiction; Great Britain -- Fiction